Lean Innovation Canvas: A Business Model to Drive the Growth of SMEs through a Mobile Delivery Application in Jaen, Peru - Pizarro Alvarez, Roger Tim (2024)
The study highlights the exponential growth of e-commerce in Peru and the increasing demand for digital services, particularly in the delivery sector. It also emphasizes the challenges faced by traditional businesses, resulting in a decline in sales for micro and small enterprises (SMEs), especially in the city of Jaen. To address this situation, the article proposes the use of an innovative approach called Lean Innovation Canvas, which combines methods such as lean startup and lean canvas. By applying lean startup, the aim is to create a robust and comprehensive model that enables the development of innovative and efficient solutions for customers. On the other hand, lean canvas helps generate a more viable business model in the market. With the implementation of this method, the intention is to develop a business model for a delivery application with the goal of promoting the growth of SMEs in Jaen, Peru.